2019
DOI: 10.1038/s41467-019-12142-4
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared light and tumor microenvironment dual responsive size-switchable nanocapsules for multimodal tumor theranostics

Abstract: Smart drug delivery systems (SDDSs) for cancer treatment are of considerable interest in the field of theranostics. However, developing SDDSs with early diagnostic capability, enhanced drug delivery and efficient biodegradability still remains a scientific challenge. Herein, we report near-infrared light and tumor microenvironment (TME), dual responsive as well as size-switchable nanocapsules. These nanocapsules are made of a PLGA-polymer matrix coated with Fe/FeO core-shell nanocrystals and co-loaded with che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
132
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(132 citation statements)
references
References 62 publications
0
132
0
Order By: Relevance
“…The photothermal conversion efficiency of hybrid ICG@GC-PP NPs at 808 nm as obtained from Figure S7, Supporting Information, is calculated to be 46.1%, which is similar to ICG-polydopamine nanodiamonds (44.5%), [41] but outperforms those of PEGylated PP (34.6%), [2a] iodinated PP (25.5%), [37a] cyanine dyes (26.6%), [42] Au@Fe 3 O 4 @PP (23.9%), [43] Au NRs (21%), and Au nanoshells (13%). [44] As ICG is one of the FDA-approved dyes for clinical use, [9] it was therefore envisaged that the biocompatibility track records of GC, PP, and ICG, would endow the proposed hybrid ICG@GC-PP nanosystem with appreciable tissue tolerance. In order to probe the in vitro toxicity of the photothermal agents, MTT assay was carried out by co-incubating various concentrations of free ICG, GC-PP, and ICG@GC-PP NPs, with mouse breast cancer (4T1) and human esophageal cancer (KYSE-30) cell lines for 24 h. As a consequence of the excellent biocompatibilities of the individual component polymers of GC-PP matrix, the high cell viability of ICG is not compromised by its loading in the dual-nanopolymer matrix.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The photothermal conversion efficiency of hybrid ICG@GC-PP NPs at 808 nm as obtained from Figure S7, Supporting Information, is calculated to be 46.1%, which is similar to ICG-polydopamine nanodiamonds (44.5%), [41] but outperforms those of PEGylated PP (34.6%), [2a] iodinated PP (25.5%), [37a] cyanine dyes (26.6%), [42] Au@Fe 3 O 4 @PP (23.9%), [43] Au NRs (21%), and Au nanoshells (13%). [44] As ICG is one of the FDA-approved dyes for clinical use, [9] it was therefore envisaged that the biocompatibility track records of GC, PP, and ICG, would endow the proposed hybrid ICG@GC-PP nanosystem with appreciable tissue tolerance. In order to probe the in vitro toxicity of the photothermal agents, MTT assay was carried out by co-incubating various concentrations of free ICG, GC-PP, and ICG@GC-PP NPs, with mouse breast cancer (4T1) and human esophageal cancer (KYSE-30) cell lines for 24 h. As a consequence of the excellent biocompatibilities of the individual component polymers of GC-PP matrix, the high cell viability of ICG is not compromised by its loading in the dual-nanopolymer matrix.…”
Section: Resultsmentioning
confidence: 99%
“…[ 8 ] Also, the ICG moiety that was embedded in Fe/FeO‐coated poly(lactic‐ co ‐glycolic) acid was responsible for the remarkable fluorescence imaging‐guided PTT of the keratin‐forming tumor cell line of HeLa cells. [ 9 ] These inspiring studies therefore establish the ability of various polymers to effectively encapsulate and convey ICG to tumor sites for fluorescence imaging, where the applied NIR (700–1100 nm) radiation could also be harnessed to achieve appreciable therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%
“…In order to tackle the crisis of antibiotic resistance, both antibiotic-free and antibiotic-strengthening strategies are being developed, such as phototherapy and photo-assisted antibiotics therapy. However, owing to the poor penetration depth of near infrared light, such strategies are only viable for subcutaneous tumors 10,11 or wound infections 12 ; they are not suitable for treating deep tissue infection. Therefore, it is urgent to develop better therapies that can effectively treat deep osteomyelitis, including MRSA infections, with minimum antibiotic toxicity.…”
mentioning
confidence: 99%
“…Nevertheless, the development of a biocompatible system which is able to combine diagnostic efficiency with the effective distribution of the drug is still the object of investigation. A study by Wang et al [ 114 ] reported the fabrication of nanostructures obtained by a combination of Poly (lactic-co-glycolic) acid (PLGA), indocyanine green (ICG) and iron-based magnetic crystals. These structures have switchable sizes (arising from the thermosensitivity of PLGA polymer), and can be loaded either with chemotherapy or photothermal agents.…”
Section: Theragnosis Applicationsmentioning
confidence: 99%